Westering women : [large type] a novel - Dallas, Sandra (Center Point Large Print, 2020)
"It's February, 1852, and all around Chicago, Maggie sees postings soliciting 'eligible women' to travel to the gold mines of Goosetown. A young seamstress with a small daughter, she has nothing to lose. She joins forty-three other women and two pious reverends on the dangerous 2,000-mile journey west. None are prepared for the hardships they face on the trek or for the strengths they didn't know they possessed. Maggie discovers she's not the only one looking to leave dark secrets behind. And when her past catches up with her, it becomes clear a band of sisters will do whatever it takes to protect one of their own"--Provided by publisher.